Analysis of 4-Hydroxy-N-Desmethyltamoxifen and Tamoxifen in Dried Blood Spot of Breast Cancer Patients By Liquid Chromatography – Tandem Mass Spectrometry - Yahdiana Harahap (Journal of Global Pharma Technology, 2018)
Tamoxifen is the first line hormonal therapy for breast cancer patients as their adjuvant therapy. The antiestrogen effect of tamoxifen is highly determined by its active metabolite, endoxifen. A simultaneous quantification method of tamoxifen and endoxifen in dried blood spot (DBS) using LC-MS/MS had been fully validated in this study. Extraction the analyte and metabolite from DBS card were conducted using methanol-acetonitrile (50:50). The separation was performed on UPLC Class BEH C18 column using 0.2% formic acid - acetonitrile as the mobile phase in gradient elution mode at 0.2ml/min. The detection of the mass was performed on Waters Xevo TQD using positive electrospray ionization for tamoxifen, endoxifen, and clomiphene as the internal standard with m/z value: 372.22>72.22; 374.29>58.2; 406.28>100.17, respectively. This method was linear in the range concentration of 5-200 ng/ml for tamoxifen and 1-40 ng/ml for endoxifen with r value 0.99. The method was applied to 40 breast cancer patients, where the results lied between 40.28 and 194.10 ng/ml for tamoxifen, meanwhile for endoxifen was 1.25 and 18.02 ng/ml. It showed that there were 4 patients received less effective tamoxifen therapy based on the endoxifen threshold in DBS sample, which was 3.3 ng/ml. This method has prospect future to optimize tamoxifen therapy by measuring tamoxifen and endoxifen concentration. Keywords: Breast cancer; Dried blood spot; Endoxifen; Tamoxifen; Clomiphene; Analysis;  LC-MS/MS; Validation.